Obdulia Cottes De Lázaro - Astol, Eugenio (My University, 1936)
El artículo de Puerto Rico Ilustrado brinda datos biográficos de Obdulia Cottes De Lázaro.
Keywords: Cottes de Lázaro, Obdulia, 1860-1930